DELEVOPING SALES INFORMATION SYSTEM USING THE PROTOTYPING METHOD IN INDONESIAN COFFEE SUPPLIERS - Fadil Aulia, Hakan Syukur; Sutomo, Rudi (Bakti Nusantara Institute, 2023)
Coffee Suppliers is a business that sells items made from coffee beans to other businesses that sell processed coffee. This firm operates on a B2B model. Coffee Suppliers' current issues include the manual recording of all inventory items and sales transactions on paper, which increases the likelihood of data reporting inaccuracies. The prototyping approach, which is a step in constructing a system with the outcomes of analysis being directly applied using a model without having to complete the entire system, is utilized in this web development. Before designing UML diagrams and building databases, the initial build identifies user requirements. To create the necessary web, the system is created using the CodeIgniter framework. It is anticipated that the construction of a web-based system will assist Coffee Suppliers in managing their business, particularly in sales, listing, and reporting, thereby lowering the possibility of data.